PENGARUH KEBIJAKAN HUTANG, RETURN ON EQUITY, NET PROFIT MARGIN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015 – 2017 - Kristanti Rahman; Fakhrudin (JURNAL EKONOMI, 2019)
Fakhrudin, Accounting Study Program Bachelor Program, STIE Muhammadiyah Cilacap Effect of Debt Policy, Return On Equity, Net Profit Margin on Company Value in Manufacturing Companies Listed in BEI 2015 - 2017. This research was conducted with the aim to determine the effect of Debt Policy, Return On Equity, Net Profit Margin on Company Value. The data used in this study is the data of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). The period used in this study is 3 years, starting from 2015 to 2017 in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). The sample selection technique uses a purposive sampling method. The type of data used is secondary data and the total sample used in this study is 64 companies that have been selected based on predetermined criteria. The data analysis method used is multiple linear regression analysis. The results showed that: 1. Debt policy has no effect on Company Value 2. Return On Equity affects Company Value 3. Net Profit Margin has no effect on Company Value. Future studies are suggested to be able to expand the research sample and add variables. Keywords: Debt Policy, Return On Equity (ROE), Net Profit Margin (NPM)